Human Rights and the Use of Force: Examining the Nigerian Government’s Response to the #EndSARS Protest - Antai, Godswill Owoche; Ekpenisi, Collins; Obisesan, Olawunmi; Umo, Maria Edet; Kolo, Eunice Awaji (NIU Journal of Educational Research, 2025)
The current study investigates the human rights violations and use of force by Nigerian government in response to #ENDSARS protest which was a nationwide protest on police brutality (mainly through Special Anti-Robbery Squad or popularly called SARS) across the nation. The analysis explores the legal setting pertaining to force used by law enforcement, allegations of human rights abuses and the place of security agencies at the events of October 20, 2020 incident at Lekki Toll Gate. Building on comparative research into international standards, such as the United Nations Basic Principles on the Use of Force and Firearms by Peacekeepers or the African Charter on Human and Peoples' Rights; the research assesses Nigerian compliance with international norms on human rights. It pinpoints the shortcomings of accountability frameworks, chastising the inadequacy of Nigeria legal as well policy making in order to protect rights of protesters. The policy recommendations proposed in the study include, but are not limited to; legal reforms; better accountability mechanisms and human rights trainings for security forces to reduce the next time bias. Recommendations to incorporate oversight mechanisms and the enforcement of recommendations from Judicial Panel of Inquiry are vital for true justice and institutional accountability. Nigeria can promote a rights-based approach to protest management, by programming and aligning domestic laws with international best practice which would serve citizens better with more human protection and restore trust in law enforcement agencies in relation to public. Keywords: Human Rights, Use of Force, ENDSARS protest, police brutality